Responsive Polydiacetylene Vesicles for Biosensing Microorganisms - Estelle Lebègue; Carole Farre; Catherine Jose; Joelle Saulnier; Florence Lagarde; Yves Chevalier; Carole Chaix; Nicole Jaffrezic-Renault (Sensors, 2018)
Polydiacetylene (PDA) inserted in films or in vesicles has received increasing attention due to its property to undergo a blue-to-red colorimetric transition along with a change from non-fluorescent to fluorescent upon application of various stimuli. In this review paper, the principle for the detection of various microorganisms (bacteria, directly detected or detected through the emitted toxins or through their DNA, and viruses) and of antibacterial and antiviral peptides based on these responsive PDA vesicles are detailed. The analytical performances obtained, when vesicles are in suspension or immobilized, are given and compared to those of the responsive vesicles mainly based on the vesicle encapsulation method. Many future challenges are then discussed.